The Effect of Age on Charitable Giving in Taiwan: Is Afterlife Consumption a Driving Force? - Chou, T.; Woodbine, Gordon (The Journal of American Academy of Business, 2012)
Researchers in both the United States and Taiwan have devoted attention to charitable giving and the factors influencing the process. Azzi and Ehrenberg's (1975) economic model in particular, their preference for using afterlife consumption as a major driving factor in charitable giving continues to attract the interest of researchers. This paper revisits the area using data from the latest available national social survey completed in Taiwan in 2008. Earlier Taiwanese studies concentrate on giving to religious entities (i.e., temples, churches and equivalent places of worship), whereas this paper examines giving to other charitable bodies, religious and non-religious and includes the views of both religious and non-religious adults. It is reported that religious affiliation acts as the major motivator to charitable giving and although giving increases with age, its association with accumulating afterlife benefits is strongly questioned.